In Silico Analysis of Sea Cucumber Bioactive Compounds as Anti-Breast Cancer Mechanism Using AutoDock Vina: In Silico analysis of sea cucumber bioactive compounds as anti-breast cancer mechanism using Autodock Vina - Yasman, S.; Yanuar, Arry; Tamimi, Zeta; Riadhi, S. Rezi (Iranian Journal of Pharmaceutical Sciences, 2020)
In recent years, the potential of marine natural products as anticancer agents, specifically for breast cancer, has been examined. The sea cucumber (Holothuroidea: Echinodermata) is known to contain triterpene glycosides, which have shown anticancer or cytotoxic activity. In this research, molecular docking of selected sea cucumber bioactive compounds was conducted on five receptor targets that play an important role in breast cancer: estrogen receptor alpha (ER-α), fibroblast growth factor receptor 1 (FGFR1), vascular endothelial growth factor receptor 2 (VEGFR2), progesterone receptor (PR), and insulin-like growth factor 1 receptor (IGFR1). The purpose of this was to observe the interaction between active compounds and the active site of breast cancer receptor targets. Holothurin A gave the lowest binding energy (-7.1 kcal/mol) and was involved in a hydrogen bond with amino acid His-516 when superposition towards to E4D cocrystal was present. Holothurin A also had a similar posing with raloxifene, in which the hydrogen bond with His-516 with a RMSD value of 3.3 Å was observed with superposition towards to the positive control raloxifene. The analysis and visualization results of 24-dehidroechinoside that was superposed on E4D cocrystal, BMI cocrystal, and positive control raloxifene showed that 24-dehidroechinoside had a hydrophobic interaction with amino-acid residue Leu-346, a strong hydrogen bond to Gln-977, as well as a hydrogen bond to Thr-347 in a distance of 3.7 Å, and a hydrophobic interaction with amino-acid residue Ala-350. The most potent in silico anti-breast cancer compounds in sea cucumbers are holothurin A and 24-dehidroechinoside. Holothurin A is active as an antibreast cancer agent by inhibiting ER-α, while 24-dehidroechinoside inhibits both ER-α and IGFR1.